2013
DOI: 10.1111/scd.12054
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of salivary total antioxidant levels and oral health status in children with Down syndrome

Abstract: In comparison to normal children, DS children showed significantly lower TAC of saliva and significantly higher salivary SA levels. In both groups of children, dental caries was higher in primary dentition when compared to their permanent dentition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 54 publications
1
33
0
2
Order By: Relevance
“…The studies were from India [25], Jordan [17], Portugal [6,14,15], Brazil [24], Turkey [11,31], the USA [32,33], China [13], Nigeria [20] and the Republic of Korea [34]. Although they presented different results, the studies by Areias (2011; 2012) used the same sample group [14,15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were from India [25], Jordan [17], Portugal [6,14,15], Brazil [24], Turkey [11,31], the USA [32,33], China [13], Nigeria [20] and the Republic of Korea [34]. Although they presented different results, the studies by Areias (2011; 2012) used the same sample group [14,15].…”
Section: Resultsmentioning
confidence: 99%
“…The articles were sorted into two groups in accordance with the description of the authors. Six studies assessed dental caries in permanent teeth, with the mean DMFT index (Decayed, Missing, and Filled Teeth) being the dependent variable analyzed [13,15,17,20,24,25]. Two studies considered all teeth (deciduous and permanent) and used a categorical dependent variable (presence or absence of dental caries) [6,14,15].…”
Section: Methodsmentioning
confidence: 99%
“…These findings are not consistent with others studies that found a significantly lower total antioxidant capacity in children with DS when compared to control. [45][46][47] In conclusion, saliva is an important tool for primary diagnosis of a possible systemic oxidative stress in patients with Down's syndrome. The present results showed a significant increase in salivary SOD concentration, MDA levels and total protein content in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…[14] This is consistent with many previous studies which reported poorer standard of oral hygiene and greater prevalence of periodontal diseases in DS children than their normal counterparts. [512151617181920] A multitude of factors may be involved in the increased susceptibility to gingival and periodontal diseases among individuals with DS. [21] Factors previously investigated include mental retardation, subgingival plaque composition, immune/inflammatory responses, and others.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Factors previously investigated include mental retardation, subgingival plaque composition, immune/inflammatory responses, and others. [202122] Microbiological studies showed that individuals with DS have significantly higher levels of periodontopathic bacteria including Porphyromonas gingivalis and Tannerella forsythensis . [17] Hence, optimal oral hygiene is of particular importance in this group in order to limit the disease onset.…”
Section: Discussionmentioning
confidence: 99%